1999
DOI: 10.1002/(sici)1098-2396(19990315)31:4<285::aid-syn6>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase a inhibition by fluoxetine: An in vitro and in vivo study

Abstract: Monoamine oxidase A (MAO-A) inhibition was investigated both in vitro and in vivo in rat brains by using the radioligand, 18 F-fluoroclorgyline (N-[3-(2Ј,4Ј-dichlorophenoxy)-2-18 F-fluoropropyl]-N-methylpropargylamine). In vitro binding affinities of six compounds, clorgyline, Ro 41-1049, deprenyl, fluoxetine, norfluoxetine and citalopram, were studied. Fluoxetine and norfluoxetine showed in vitro affinities of 36.5 and 68 µM for MAO-A, respectively. Fluoxetine and norfluoxetine also significantly inhibited (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The therapeutic action of fluoxetine primarily results from the inhibition of serotonin reuptake (Stark et al, 1985;Wong et al, 1995), thus enhancing serotoninergic neurotransmission. Besides this mechanism, fluoxetine has several other modulatory effects, such as inhibition of G protein-coupled receptors (Stanton et al, 1993;Palvimaki et al, 1996), blockade of monoamine oxidases (Mukherjee and Yang, 1999), and modulation of several ionic channels. Indeed, it has been reported that fluoxetine is a potent blocker of K ϩ channels (Thomas et al, 2002;Choi et al, 2003;Kobayashi et al, 2003;Kennard et al, 2005), Na ϩ channels (Pancrazio et al, 1998), and Ca 2ϩ channels (Deak et al, 2000).…”
supporting
confidence: 76%
“…The therapeutic action of fluoxetine primarily results from the inhibition of serotonin reuptake (Stark et al, 1985;Wong et al, 1995), thus enhancing serotoninergic neurotransmission. Besides this mechanism, fluoxetine has several other modulatory effects, such as inhibition of G protein-coupled receptors (Stanton et al, 1993;Palvimaki et al, 1996), blockade of monoamine oxidases (Mukherjee and Yang, 1999), and modulation of several ionic channels. Indeed, it has been reported that fluoxetine is a potent blocker of K ϩ channels (Thomas et al, 2002;Choi et al, 2003;Kobayashi et al, 2003;Kennard et al, 2005), Na ϩ channels (Pancrazio et al, 1998), and Ca 2ϩ channels (Deak et al, 2000).…”
supporting
confidence: 76%
“…These discrepant results could be explained by several factors. The affinity of clorgyline for MAO-A is much less than that of befloxatone (Curet et al, 1996;Mukherjee and Yang, 1999). Clorgyline and befloxatone behave differently in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, citalopram was found to have a lower affinity for MAO-A and B compared to fluoxetine and no inhibitory action on the binding of clorgyline and methylpropargylamine to either MAO-A or MAO-B. 24,44 The competing for binding sites depends however on both, the affinity as well as the respective concentrations of the compounds. The extent to which citalopram in a therapeutic setting may interfere with the metabolism of monoamine substrates catalysed by MAO in the brain remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…23 In general, antidepressants, including those SSRIs examined so far, have only weak, if any, MAO inhibitory activity. [24][25][26] Presumably, the syndrome which appears after combining SSRIs with MAO inhibitors stems from a synergistic action on the levels of serotonin in the synaptic cleft. Whether such effects could arise through mutual inhibition of each drug's inactivation remains an open question.…”
Section: Introductionmentioning
confidence: 99%